2022
DOI: 10.3390/su14138157
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Regulations and Social Norms on Farmers’ Chemical Fertilizer Reduction Behaviors: An Investigation of Citrus Farmers in Southern China

Abstract: This study investigates how environmental regulations and social norms affect farmers’ chemical fertilizer reduction behaviors (CFRBs) and investigates the mediating role played by social norms and the moderating role played by social networks. As the analysis tool, a structural equation model is employed to analyze the data collected from a questionnaire survey with 402 valid samples of Chinese citrus growers. This study reveals that (1) environmental regulations and social norms have a significant effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The effectiveness of the environmental management authorities in developing countries in ensuring compliance of MSMEs with environmental protection standards is compromised by gaps and weaknesses in environmental regulatory frameworks and lack of funding and expertise (Eskeland & Jimenez, 1992). The potency of such weak regulatory power to induce MSMEs' compliance with environmental regulations leans heavily on institutional trust of the regulatory agencies by owners of MSMEs (Cui & Liu, 2022). Even in the presence of sufficient regulatory power as in developed countries, Rhodes et al (2017) proposes that compliance with regulations is a function of trust in the institutions since people might not have sufficient time or skills to independently assess the regulated issues.…”
Section: The Moderating Role Of Institutional Trust In the Effect Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of the environmental management authorities in developing countries in ensuring compliance of MSMEs with environmental protection standards is compromised by gaps and weaknesses in environmental regulatory frameworks and lack of funding and expertise (Eskeland & Jimenez, 1992). The potency of such weak regulatory power to induce MSMEs' compliance with environmental regulations leans heavily on institutional trust of the regulatory agencies by owners of MSMEs (Cui & Liu, 2022). Even in the presence of sufficient regulatory power as in developed countries, Rhodes et al (2017) proposes that compliance with regulations is a function of trust in the institutions since people might not have sufficient time or skills to independently assess the regulated issues.…”
Section: The Moderating Role Of Institutional Trust In the Effect Of ...mentioning
confidence: 99%
“…The strength of enforcement in inducing compliance to environmental standards is likely to be facilitated by trust in the institutions that enact laws and policies, or those that exercise government authority to enforce the laws and policies (Cui & Liu, 2022). Institutional trust has been linked with enhanced compliance to environmental regulations in a variety of settings (see e.g., Cvetkovich, Siegrist, Murray & Tragesser, 2002;Fairbrother, Johansson Sevä & Kulin, 2019;Kulin & Johansson Sevä, 2021;Greenstone & Hanna, 2014;Hammar & Jagers, 2006;Rhodes, Axsen & Jaccard, 2014;Harring & Jagers, 2013;Jagers & Hammar, 2009;Kallbekken & Saelen, 2011;Kitt, Axsen, Long & Rhodes, 2021;Siegrist, Cvetkovich & Roth, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Concientizar a los agricultores a reducir la utilización de fertilizantes químicos [53] China fijó un nuevo objetivo más alto para controlar las emisiones de gases de efecto invernadero para 2020, para lograr este objetivo, China está liderando el mundo en términos de capacidad hidroeléctrica instalada y también aumentando la capacidad de almacenamiento. Además de alcanzar el 20,36% de superficie forestal, la capacidad de construcción de energía eólica, áreas de captación de energía solar y centrales nucleares.…”
Section: Socialunclassified
“…Yang et al (2021) found that the fertilizer reduction effect of agricultural subsidies was positively related to the degree of part-time farming. A study by Cui and Liu (2022) on 402 citrus growers in China showed that the government's services and subsidies for green agriculture had a significant incentive effect on farmers' chemical fertilizer reduction behavior, and the effect was greater for larger farmers; the stronger the awareness of green agriculture among farmers' neighbors, the greater this effect would be. Niu et al (2022) argued that policy agricultural insurance pilots exacerbated fertilizer surface source pollution in China, and this effect was relatively more pronounced in eastern and high disaster areas.…”
Section: Literature Reviewmentioning
confidence: 99%